PDT combined with liquid nitrogen cryotherapy is superior to PDT alone in Actinic Keratosis - Xianmin Meng; Chaofeng Xia; Hong Luan; Wenhui Liu; Yongguo Li (Photodiagnosis and Photodynamic Therapy, 2025)
Background: Actinic keratosis (AK) possesses the potential to progress into squamous cell carcinoma (SCC). Aminolevulinic acid photodynamic therapy (ALA-PDT) is acknowledged as a preferred treatment modality for AK. To improve clinical clearance rates, combination strategies that integrate PDT with other therapeutic approaches are often utilized. This study seeks to assess the therapeutic efficacy and safety profile of combining cryotherapy with PDT in the management of AK. Methods: In this single-center study, 66 patients with histopathologically and/or dermatoscopically confirmed actinic keratosis were enrolled. Participants were randomly allocated into two groups: one receiving liquid nitrogen cryotherapy combined with photodynamic therapy (LN-PDT) and the other receiving control photodynamic therapy (C-PDT), comprising 35 and 31 patients, respectively. Follow-up was conducted for a minimum duration of 6 months. Dermoscopy follow-up examinations were systematically performed at 3-month and 6-month intervals post-final treatment. The primary outcome measure was the rate of initial complete clearance at the 3-month mark, whereas the secondary outcome focused on sustained complete clearance at 6 months. Treatment efficacy and adverse reaction profiles were meticulously documented and underwent comparative analysis between the two therapeutic groups. Results: At the 3-month follow-up post-final treatment, the initial complete clearance rates were 93.6 % and 68.4 % in the two respective groups, indicating a statistically significant difference (P < 0.05). At the 6-month follow-up, sustained complete clearance rates were 95.1 % and 72.6 % in the respective groups, with similarly significant intergroup statistical differences P < 0.05). Conclusion: For the treatment of actinic keratosis (AK) lesions, the combination of liquid nitrogen cryotherapy and photodynamic therapy was more therapeutically effective than photodynamic therapy alone.